S*-PROPER FUNCTIONS - No'man, Laheeb Muhsen (Al-Nahrain Journal of Science, 2018)
The main aim of this work is to study some types of proper functions, namely, s*-proper functions and we equivalent the definition of s*-proper function by a new definition depending on filters. And we prove some propositions on this subject by using the last definition and we get some results about s*-proper functions.